Design of BPJS Claim Information System for Hemodialysis Patients using the V-Model method - Hanifah, Nabila Khaerunnisa; Kamilia, Nala; Gunawan, Erix; Syahidin, Yuda; Sukmawijaya, Jeri (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
This study aims to describe the information system for filing outpatient BPJS claims for hemodialysis poly and identify databases, inputs and outputs, and interfaces that are adjusted to process the outpatient BPJS claim filing data. The research method applied is the V-Model method. The tools used in the process of system planning and development are Flowchart, Data Flow Diagram (DFD), and Entry Relationship Diagram (ERD). The results of the analysis of the design of this system will be tested for feasibility using Microsoft Visual Studio-based applications. Based on this research, it can be concluded that there are still much incomplete patient data, in the hemodialysis poly unit,  which affects the activities in claiming BPJS  files for hemodialysis patients.